Utilization of Polyethylene Terephthalate (PET) in Bituminous Mixture for Improved Performance of Roads - A. F., Ahmad; A. R., Razali; I. S. M., Razelan; S. S. A., Jalil; M. S. M., Noh; A. A., Idris (IOP Publishing, 2017)
Plastic bottle for recycling can be found from the household waste stream, and most of them are made from Polyethylene Terephthalate. In this research, PET is utilized to explore the potential prospects to upgrade asphalt mixture properties. The objectives include deciding the best measure of PET to be used. For experimental, Marshall mix design was utilized to determine the ideal bitumen binder content and to test the modified mixture properties. The samples were created per the requirement for aggregate course wearing (ACW14) using the Standard Specification of Road Work (SSRW) in Malaysia. 20 samples were utilized to determine the binder content, and 30 samples were used to research the impact of modifying asphalt mixtures. 2%, 5%, 10%, 15% and 20% of PET by weight of the optimum binder content (4.8%) were tested. Optimum PET content is 10%, and the result shows a good stability with 16.824kN, 2.32g/cm3 bulk density, void filled with bitumen (VFB) with 71.35%, flow with 3.2248mm, air void (AV) with 4.53%, and void of mineral aggregate (VMA) with 15.15%. The outcomes showed that PET modifier gives better engineering properties. Therefore, 10% of PET by the weight of binder content was suggested as the best amount of the modifier